ISOLATION AND STRUCTURAL ELUCIDATION OF FLAVONOID FROM BOESENBERGIA PANDURATA RHIZOME - Moch Abdussalam; Juniarti; Indah Permata Yuda (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Temu Kunci (Boesenbergia pandurata) rhizome constitutes a botanical resource long harnessed for ethnomedicinal applications among localized populations. To validate its long-standing traditional application, this investigation aimed to characterize the bioactive chemical profile of the Boesenbergia pandurata rhizome. The dried, pulverized rhizome was initially subjected to maceration for crude extraction of secondary metabolites, followed by a meticulous purification sequence. Vacuum Liquid Chromatography (VLC) was first employed for bulk separation, and subsequent Radial Chromatography refined the flavonoid-rich fractions to yield a pure isolate. The structure of this isolate was then conclusively resolved using advanced 1H-NMR and 13C-NMR spectroscopy, which unambiguously identified the primary compound as pinostrobin.